The importance of detailed data utilization on the performance evaluation of a grid-independent hybrid renewable energy system - Erdinc, O.; Uzunoglu, M. (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
In this study, a multi-source hybrid power system consisting of wind turbine (WT), photovoltaic (PV) solar unit, proton exchange membrane (PEM) FC and battery is proposed. The WT and PV generation systems are considered as the main power sources for utilizing the available renewable energy. The FC system is proposed as the back-up generation combined with electrolyzer unit and battery picks up the fast load transients and ripples. In such a hybrid system, energy management plays an important role for the overall system performance and durability. From this perspective, a fuzzy logic based intelligent controller is considered in this study. Besides, a detailed minute-scale meteorological and load demand data is utilized in the simulation process and the importance of utilization of such detailed data is presented. This detailed analysis may be valuable for evaluating the feasibility of grid-independent hybrid renewable energy units for upcoming power systems. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Fuzzy logic; Hybrid system; PEM fuel cell; Photovoltaics; Renewable energy; Wind turbine; POWER-GENERATION SYSTEM; SIMULATION; MANAGEMENT; MODEL; STORAGE; DESIGN; LOAD; Chemistry; Electrochemistry; Energy & Fuels